Birth Weight and Linear Body Measurements of Saburai Goats: Influence of Sex and Birth Type - Kunaifi Wicaksana; Anggi Derma Tungga Dewi; Lusia Komala Widiastuti; Herdiyon Banu Sanjaya (ANIMAL PRODUCTION, 2026)
This study aimed to evaluate the effects of sex and birth type on birth weight and linear body measurements of Saburai Goats at different age groups (0, 3, 6, 9, and 12 months of age). The study used secondary data from 76 Saburai Goats raised in Lampung Province. Data were obtained from farm records and included birth weight, chest circumference, body length, ear length, and withers height. The data were analyzed using an independent t-test to compare differences between groups. The results showed that male goats had significantly (P<0.05) higher birth weight (3.99 ± 1.62 kg) than females (2.76 ± 0.44 kg). In single births, male goats (5.26 ± 1.40 kg) had significantly (P<0.05) higher birth weight than females (3.79 ± 0.79 kg), while in twin births, no significant difference was observed (P>0.05). Birth weight in single births was significantly higher than in twin births for both sexes (P<0.05). Body size measurements, including chest circumference, body length, ear length, and withers height, were generally higher in males than in females across age groups. In conclusion, sex and birth type significantly affected the birth weight of Saburai goats, with males and single-born kids showing higher birth weight than females and twins, respectively. The independent t-test analysis revealed that the effect of sex on linear body measurements was parameter- and age-dependent. Specifically, body length and withers height were consistently greater in males across all age groups, while chest circumference and ear length showed significant differences between sexes only at certain ages. These findings suggest that sex and birth type are important factors to consider in selection and breeding programs for Saburai Goat.